The Meaning of Basudara in South Titiwungen Settlement Post Reclamation of Manado Beach - Subroto, T. Yoyok Wahyu (Faculty of Engineering, Sam Ratulangi University, 2009)
This research is about settlement society in Titiwungen Post Reclamation in Manado Beach. The research method and paradigm were used is phenomenology by Husserl. Data collection is carried out by doing interview and observation meanwhile the analysis method is inductive method. This research found that basudara in the settlement becomes a unity in society and this unity was formed as the groups of Minahasan society. The meaning of basudara in residence society is formed as first as heredity from generation. Second is the unity value as resemblance, understanding, compromise, tolerance and communication between the society and third refers to the space continuity of society in the settlement.